Exploring the school personnel's perceptions of the successful school management and effective leadership behaviors - Waemusor, Inham (Institute of Education, International Islamic University Malaysia, 2010)
It cannot be denied that a successful and effective school must be led by an effective leader. Even Islamic Private schools are popular in Southern Thailand but most of them are unqualified. The greatest obstacle to the development is found into school management and leadership behaviors. This study represents an attempt to quantify attitudes of school personnel toward the characteristics of successful school management (SSM) and effective leadership behaviors (ELB) of the principals. Two set of questionnaires that measure two factors that contributed to an effective school were employed on 384 samples among principals, managers, and teachers who worked in Islamic private schools in Pattani. The major findings that emerged were as follows: a) Vision was overall rated as the most important factor of successful school management (m = 4.32), Professional development was generally the least important factor (m = 3.98), b) With respect to the effective leadership behaviors of school principals, Culture of learning and professional behavior and supporting process of principals found to be highest and rated under the basic level of standard performance (m = 3.20, 3,.31), while rigorous curriculum and planning process were found to be lowest effective and below basic level based on the standard of performance (m = 2.87, 2.94), and c) all factors that shared the same characteristic were found to be correlated but only showed a few correlation across factors, whereby five of SSM were correlated with planning and some of the key processes and all domains in ELB were significantly correlated with all of the key processes. Above all, the result from this study could give an insight understanding to principals, school personnel, as well as Private Islamic School in Southern Provinces Association and other related organizations on how to develop an effective school considering all the factors measured.